Magnesium and Osteoporosis: A Meta-Analysis of the Effects on Bone Turnover Markers, Fracture Incidence, and Quality of Life - Sari, Mia Indah; Surya Darma (HM Publisher, 2025)
Background: Osteoporosis, a prevalent bone disease characterized by reduced bone mineral density (BMD) and increased fracture risk, poses a significant public health challenge. Magnesium, an essential mineral involved in bone metabolism, has emerged as a potential therapeutic agent. This meta-analysis aimed to evaluate the effects of magnesium supplementation on bone turnover markers, fracture incidence, and quality of life in individuals with osteoporosis. Methods: A systematic search of PubMed, Embase, and Cochrane Library databases was conducted from January 2013 to December 2024 to identify randomized controlled trials (RCTs) investigating the impact of magnesium supplementation on adults diagnosed with osteoporosis. The primary outcomes were changes in bone turnover markers (serum calcium, phosphorus, alkaline phosphatase, and osteocalcin), fracture incidence, and quality of life scores. Standardized mean differences (SMD) and risk ratios (RR) with 95% confidence intervals (CI) were calculated using random-effects models. Results: Nine RCTs met the inclusion criteria, encompassing a total of 825 participants. Magnesium supplementation demonstrated a significant improvement in bone turnover markers, with a decrease in serum alkaline phosphatase (SMD = -0.35; 95% CI: -0.62, -0.08; p = 0.01) and osteocalcin (SMD = -0.29; 95% CI: -0.51, -0.07; p = 0.009). A trend towards reduced fracture incidence was observed in the magnesium group (RR = 0.72; 95% CI: 0.51, 1.02; p = 0.06). Furthermore, magnesium supplementation significantly improved quality of life scores, as measured by the Osteoporosis Quality of Life Questionnaire (OQLQ) (SMD = 0.41; 95% CI: 0.15, 0.67; p = 0.002). Conclusion: This meta-analysis provides evidence that magnesium supplementation may have beneficial effects on bone turnover markers and quality of life in individuals with osteoporosis. Although a trend towards reduced fracture incidence was observed, further large-scale RCTs are warranted to confirm this finding.